Current Status and Trends of Minimally Invasive Gastrectomy in Korea - Shin-Hoo Park (MDPI AG, 2021)
Since its introduction in the early 1990s, laparoscopic gastrectomy has been widely accepted for the treatment of gastric cancer worldwide. In the last decade, the Korean Laparoendoscopic Gastrointestinal Surgery Study group performed important clinical trials and exerted various efforts to enhance the quality of scientific knowledge and surgical techniques in the field of gastric cancer surgery. Laparoscopic gastrectomy has shifted to a new era in Korea due to recent advances and innovations in technology. Here, we discuss the recent updates of laparoscopic gastrectomy—namely, reduced-port, single-incision, robotic, image-guided, and oncometabolic surgery.